Short Communication: Note on the genus Dorstenia Plum. ex L. (Moraceae) in Java (Indonesia) and noteworthy information on the identity of D. bahiensis through ITS sequence (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Irsyam ASD, Hariri MR, Peniwidiyanti, Irwanto RR. 2021. Short Communication: Note on the genus Dorstenia Plum. ex L. (Moraceae) in Java (Indonesia) and noteworthy information on the identity of D. bahiensis through ITS sequence. Biodiversitas 22: 3358-3363. Dorstenia Plum. ex L. grouped within tribe Dorstenieae in the Moraceae. The genus comprises 105 species that are distributed in the African, Asian, and Neotropical regions. Previous studies showed that Java Island has only one species of Dorstenia, namely D. contrajerva L. This exotic species was introduced a long time ago and naturalized in Java. The field survey was carried out in Banten, Jakarta, West Java, and East Java. Herbarium study was also carried out in Herbarium Bogoriense and Herbarium Bandungense. There are two additional species from Java, D. bahiensis Klotzsch ex Fisch. and C.A. Mey. and D. foetida (Forssk.) Schweinf. Dorstenia bahiensis originated from Eastern Brazil and was found naturalized in Mekarwangi Village, Lembang, Bandung Barat regency, Indonesia. Dorstenia foetida is native to Africa and is only found as a popular cultivated plant. A molecular approach was carried out to provide the right identity of D. bahiensis because it has been mistakenly labeled as D. elata by a Javanese horticulturist. The internal transcribed spacer (ITS) sequence separated and distinguished both D. bahiensis and D. elata into different clades, which makes the popular name for D. elata actually D. bahiensis. Based on this study, there are three species of exotic Dorstenia in Java. The descriptions, photographs, and further discussions are provided.
Keywords: alien; Dorstenia; Java; Moraceae; tusuk konde